MANAGING ORGANIZATIONAL BEHAVIOR IN INCREASING EMPLOYEE ENGAGEMENT BASED ON SACRED MOTIVATION IN PESANTREN - Rosi, Fathor; Hasanah, Uswatun; Rofiki, Moh (Nurul Jadid University, 2022)
This study aims to determine organizational behavior in increasing employee engagement based on religious motivation. The forms of involvement of educators and educational staff discussed in this study are personal engagement and organizational engagement. The research approach used is qualitative with the type of case study. Collecting data using observation techniques, in-depth interviews, and documentation. After the data was collected, the researcher used the Miles and Huberman data analysis technique, which consisted of data reduction, data display, and verification to analyze the data and draw research findings. This study indicates that the form of involvement of educators and educational staff in Pesantren consists of personal engagement, which is the motor of organizational engagement and cultural engagement. Meanwhile, the management is carried out by building harmony and harmony, capability, and spiritual leadership.